Efektivitas Proses Audit Di Era Masyarakat 5.0 - Hariyani, Azkia; Muluk, M. Adrian (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
Increasingly complex financial transactions require auditors to identify and analyze material misstatements in financial statements accurately and precisely within a reasonable timeframe, making audit process effectiveness a critical issue. This study examines the effects of artificial intelligence, big data analytics technology, and computer-assisted audit techniques on audit process effectiveness using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. Data were collected through questionnaires distributed to 70 external auditors working in public accounting firms in South Jakarta and were analyzed using SmartPLS version 4.1. The findings indicate that the use of artificial intelligence and big data analytics technology does not have a significant effect on audit process effectiveness, whereas the use of computer-assisted audit techniques has a significant positive effect. These results provide practical insights for public accounting firms to enhance human resource readiness, organizational support, and technological infrastructure to optimize the use of modern audit technologies and improve audit process effectiveness. From a theoretical perspective, this study extends the application of the UTAUT framework by providing empirical evidence on the role of modern audit technologies in shaping audit process effectiveness within the Indonesian auditing context.